Raising Growth and Investment in Sub-Saharan Africa : What Can be Done? - Hernandez-Cata, Ernesto (IMF Policy Discussion Papers; Policy Discussion Paper, 2000)
This paper argues that sub-Saharan Africa's growth performance needs to be improved substantially in order to raise standards of living to an acceptable level and achieve a visible reduction in poverty. The paper provides a broad overview of the explanations for sub-Saharan Africa's unsatisfactory growth performance in the past, paying particular attention to the empirical literature. It argues that growth has been hampered by economic distortions and institutional deficiencies that have increased the risk of investing in Africa, and lowered the rates of return on capital and labor as well as the growth of total factor productivity.